Are fair value options created equal? A study of SFAS 159 and earnings volatility. (September 2017) - Couch, Robert; Thibodeau, Nicole; Wu, Wei
Abstract: The fair value option (FVO) embedded in both SFAS 159 and IAS 39 was introduced to allow firms to reduce earnings volatility induced from mixed-measurement accounting. Fiechter (2011) finds a reduction in earnings volatility among IAS 39 FVO adopters. In contrast, we find that earnings volatility increased among U.S. financial institutions following SFAS 159 FVO adoption in 2008. In further analysis, we find that this result is driven by firms reporting fair value assets without reporting fair value liabilities. Our study uses a two-stage Heckman regression to control for treatment effects, and our findings are robust to difference-in-differences regressions with control samples constructed by propensity score matching. These results have implications for current debates regarding fair value accounting, accounting choice, and earnings volatility of financial institutions.